On the estimation of stability and control characteristics of a generalised forward swept wing aircraft - Heydari, F. (Cranfield University, 1986)
Recent advances in composite structures and active control systems have made the concept of a forward swept wing aircraft a viable alternative to the more conventional configurations. This thesis encompasses some of the work resulting from a three year research program covering the dynamic behaviour and characteristics of a FSW aircraft having a closely coupled canard. The dynamic model has been based on the output of a first order optimisation routine with emphasis on minimum induced drag and static margin as the two most important criteria. Stability characteristics of the dynamic model were extracted from the transient response tests in both longitudinal and lateral modes by means of a statistical method, namely Extended Kalman Filter (E. K. F. ). In carrying out the dynamic tests, use was made of the facilies outlined by Ref. 8. Validated through computer based experiments, the Extended Kalman Filter algorithm has successfully been applied to the open-loop wind tunnel tests. Simulations of the equations of motion using estimates of stability derivatives obtained in this way closely match the observed behaviour. Furthermore, substitution of aerodynamic data obtained via static wind tunnel measurements in theoretically derived expressions for some of the stability derivatives has resulted in an alternative set of stability derivative estimates. ' Finally, estimates of the stability derivatives obtained with the E. K. F., first order optimisation program and static tests are compared. Although the results are limited to very low subsonic Mach numbers, nevertheless, they are very encouraging. It is hoped that future work might extend the studies into unstable flight regimes.